Discriminatory influence of Pinpoint perfusion imaging on diversion ileostomy after laparoscopic low anterior resection. (October 2015) - Ris, F.; Buchs, N. C.; Morel, P.; Mortensen, N. J.; Hompes, R.
Abstract: While still debated, it was advised to perform a protective temporary ileostomy after a low anterior resection (LAR). This might help to decrease the leak rate and therefore offers the patient better outcomes. Anastomotic leak can occur in many situations after a LAR and the control of the risk factors helps to adapt the need of an ileostomy. Near infrared technology allows assessing the microvascularisation of the anastomosis at the time of surgery and therefore might be an important tool to avoid a stoma in given situation. This article reviews the evidences with the use of this technology.